CHANGING PATTERNS IN RARE RED BLOOD CELL (RBC) PHENOTYPES, AND ANTIBODIES – RESULTS FROM MELBOURNE RBC REFERENCE LABORATORY. (February 2015) - Lukito, Pohan; Ramadi, Lanny; Condon, Jenny; Aung, Ni Ni; Hogan, Chris; Nedeljkovic, Marija
Abstract : Aim: Red cell antigen phenotypes vary between different ethnic groups. The demographics of the Australian population have changed with waves of immigration. We examined whether this impacts observed patterns of red cell phenotypes and allo-antibodies. Methods: We reviewed results on patient samples referred to our laboratory in two cohort periods: 1997 and 2012. Results: For the 2 cohort years 1997 and 2012 we observed: (242, 537) antibodies identified in (148, 351) patient samples. Antibody frequencies: Rh (28%, 30%), K (7%, 4%), Fy (7%, 5%), Jk (6%, 4%), ≥2 alloantibodies (41%, 38%). Three patients were identified with the Jk(a-b-) phenotype in 1997 (2%), and six in 2012 (1.7%). For the Fy(a-b-) phenotype, in 1997 no patients were reported. In 2012 there were seven patients with this phenotype. Conclusion: Comparing our 1997 and 2012 cohorts, we observed no major change in the pattern of the clinically significant red cell allo-antibodies. There was an increased number of patients with Fy(a-b-) phenotype. This likely reflects immigration from Africa over the last decade. Providing compatible blood for these patients can be challenging. We encourage blood donation from diverse ethnic groups, to enrich the range of red cell phenotypes available to patients.